Alginate and derivatives hydrogels in encapsulation of probiotic bacteria: An updated review. (April 2023) - Nezamdoost-Sani, Narmin; Khaledabad, Mohammad Alizadeh; Amiri, Saber; Mousavi Khaneghah, Amin
Abstract: Natural hydrogels such as alginate are hopeful gadgets for cellular encapsulation, drug delivery, and many others because of their properties, such as biodegradable and non-toxic for the environment. Probiotics, as intestinal microbiota, have numerous benefits for the host's health. On the other hand, the survival of probiotics is critical, especially in the food and medicine industry, and probiotics should endure disagreeable status that occurs in passing through the gastrointestinal system. Encapsulation can be applied to protect probiotics but increase their bio-accessibility, so the survival rate of bacteria and their transportation to different body parts. In this review, the literature on delivery systems results focuses on combining alginates with other biopolymers to produce hydrogels that enclose probiotics, only increasing their encapsulation performance and survival compared to alginates in gastrointestinal simulation conditions collected. All the tastes and limitations, along with the benefits of microencapsulation of probiotics using hydrogels, can lead to the emergence of biopolymers, new ways of protecting probiotics, and ultimately producing products that are safe for consumers. Graphical abstract: Image 1 Highlights: Microencapsulation can shelter probiotics from noxious environmental. Natural hydrogels such as alginate are promising systems for delivery of probiotics. Alginate hydrogels are biologically inert materials applied in medical and food industries.